Planktonic equatorial diversity troughs: fact or artifact? Latitudinal diversity gradients in Radiolaria. Issue 1 (9th December 2016) - Boltovskoy, Demetrio; Correa, Nancy
Abstract: In contrast to the classical notion of an increasing biodiversity from the poles to the equator, a number of studies concluded that the diversity of marine species is highest at the middle latitudes, and decreases at the equator. Using a worldwide database critically compiled from 72 surveys (307 species, 4, 807 water column and surface sediment samples), we analyzed the latitudinal gradients in species richness (LGSR) of a highly diversified group of marine holoplanktonic protists, the polycystine Radiolaria. Species richness values were corrected for uneven sample coverage and sample size, and contrasted with gradients in 11 environmental variables. Radiolarian species richness decreases from the equator to the poles both in the water column and in the surface sediments and is tightly coupled with temperature throughout the entire thermal range of marine waters. In the tropical Pacific Ocean, a conspicuous east‐west gradient in diversity is also associated with temperature. Globally, diversity is negatively correlated with mean annual concentrations of nutrients (N, P, Si) and chlorophyll a. Disagreements with results reported for many other oceanic plankton may stem from the reduction of 3D distributional patterns onto 2D or 1D spaces, to the intermittent mixing of Subtropical and Subpolar species at the middle latitudes, and to a Mid‐Domain Effect. The fact that radiolarian LGSR do not show this drop at the equator is partly due to methodological and database‐related differences, and probably also in part a reflection of taxon‐specific traits.